Pemanfaatan Sampah Melalui Teknik Reuse Dan Recycle Pada Mahasiswa Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo - Wa Ode Winesty Sofyani; Benny Baskara; Ashmarita Ashmarita; Hidayah Rahman (Pusat Riset dan Inovasi Nasional, 2025)
Effective waste management is crucial for environmental sustainability. Utilizing waste through reuse and recycle techniques serves as a solution to mitigate the negative impacts of waste. This community service aims to educate students of the Department of Anthropology, Faculty of Cultural Sciences, Universitas Halu Oleo, on the reuse and recycle techniques as an environmentally friendly waste management approach. The service partners are students who participate in training and socialization on how to repurpose used materials into useful products. The methods used include socialization, training, and hands-on practices related to repurposing used items such as plastic bottles, paper, and cardboard into crafts. The results of the community service show that the knowledge transfer through the provided counseling and training has motivated the participants to utilize waste produced daily and scattered waste in their living environment. Through the two techniques taught, participants were able to produce various products from materials once considered waste, transforming them into functional, artistic, and even edible items. The products created included bags, tissue holders, accessories, and snacks.